Aliran Sesat, Toleransi Agama, Dan Pribumisasi Islam Humanis - Choirul Mahfud (Ulumuna, 2007)
Religious “splinter groups” can be found in any established religions, such as Islam, and become an interesting discourse to deal with today. The emergence of such groups can be viewed either as critics to the religious mainstream interpretation and/or practices or responses to the contemporary complex problems of modernity in terms of its relation to religious believe. The recent case of Ahmadiah and Al-Qiyadah Al-Islamiyah in Indonesia are among very controversial phenomena of “splinter groups” that resulted in debates and tensions among muslims communities. This article is aimed at observing the phenomena and answering some crucial questions, such as why they emerge, how do mainstreams of Indonesian muslims response to them, and what are their impacts on the future of intra and inter religious tolerance in Indonesia.